Public Service Transformation during the Covid 19 Pandemic by the General Election Commission of Bandung Regency in the Local Election (Pilkada) - Tatang Sudrajat (JIAPI: Jurnal Ilmu Administrasi Dan Pemerintahan Indonesia, 2021)
This study aimed to elaborate the transformation of services provided by the General Election Commission of Bandung Regency during the Covid 19 pandemic to all election stakeholders in all stages of the election such as voters, political parties, administrators, candidate pairs, election supervisors, election observers, election desks and other parties. It also analysed the substance of all local elections regulations as a form of policy for the implementation of local elections during the Covid-19 pandemic. This study used qualitative method with in-depth interview and documentation. The result of this study indicated that there was a transformation of public services that relied on communication and information technology, such as updating voter data, socialization and voter education, nomination of candidate pairs, campaigning, as well as voting and counting votes.